Understanding psychological symptoms among Chinese college students during the COVID-19 Omicron pandemic: Findings from a national cross-sectional survey in 2023 - You Xin; Tianrui Ren; Xu Chen; Xin Liu; Yijin Wu; Shu Jing; Ling Zhang; Zhenwei Dai; Ye Wang; Xiaoyou Su (Comprehensive Psychoneuroendocrinology)
During the Omicron pandemic in late 2022, this study surveyed Chinese students via an online questionnaire to assess their mental health status, prevalence of psychological symptoms, and associated factors. A nationwide cross-sectional survey of 4254 participants was conducted in seven regions of China from January 5 to February 9, 2023. Scales were utilized respectively to measure depressive symptoms, anxiety symptoms, post-traumatic stress disorder (PTSD) symptoms, and perceived social support. Descriptive, univariate, and multivariable analyses were performed to identify associated factors. Protective factors against depressive symptoms include regular exercise and robust social support networks, while risk factors involve excessive alcohol consumption, comorbidities, Omicron infection, and irregular sleep patterns. Risk factors for anxiety symptoms include comorbidities, Omicron infection, living alone, and irregular sleep patterns, while social support emerges as a protective factor. For PTSD symptoms, regular exercise and strong social support systems are identified as protective measures, with risks associated with comorbidities, Omicron infection, and poor sleep quality. Students are particularly vulnerable during the pandemic due to their lifestyle and academic pressures. It's essential to bolster their social support and promote healthier habits.